Teori Pemrosesan Informasi dalam Model Pembelajaran di SD/ MI - Setia Budi, Irwan (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
This information processing theory is based on the assumption that learning is a very important factor in development. Development is the cumulative result of learning. In learning there is a process of information, to be processed so as to produce a form of learning outcomes. In information processing, there is an interaction between internal conditions and individual external conditions. Information is knowledge gained from learning, experience or instruction. So the theory of information processing contains an understanding of how individuals perceive, organize, and remember the large amount of information that individuals receive from the environment. The brain working process and the mechanism of information processing theory are divided into several stages, including: a) Stimulus from the Environment; b) holding centers; c) short term memory (short term memory); d) transfer of short-term memory to long-term memory; e) long term memory (long term memory); f) planning center; g) implementing tools. The application of Information Processing Theory in Learning in SD/MI is divided into three, namely: Food organizer, learning state, and cognitive content.